Field performance evaluation of pervious concrete pavement reinforced with novel discrete reinforcement. (June 2019) - AlShareedah, Othman; Nassiri, Somayeh; Chen, Zhao; Englund, Karl; Li, Hui; Fakron, Osama
Abstract: Pervious concrete (PC) pavements are used for stormwater management and flood mitigation. However, the highly porous macrostructure of PC results in low mechanical properties compared to portland cement concrete (PCC). Cured Carbon Fiber Composite Material (CCFCM) is heavily used in manufacturing of high-performance products. Therefore, large quantities of excess CCFCM materials are generated, requiring proper disposal and reuse applications. In this study, recycled CCFCM were used as discrete structural reinforcement in a PC pavement demonstration project. In addition to one Control section, two pavement sections were paved using PC mixed with 0.27 and 0.40% volume fractions of CCFCM, respectively. Field cores and cast specimens from CCFCM-PC mixes achieved similar 7 and 28-day flexural, tensile, and compressive strengths to the Control, although their porosity was higher. Furthermore, CCFCM-PC sections had higher infiltration rates than the Control. Using lightweight deflectometer load testing, CCFCM-PC pavement sections showed lower surface deflection than the Control under the same applied load. Based on these findings, CCFCM was successfully implemented as reinforcing elements in PC, providing an environmentally-friendly solution to recycle this material.